2015
DOI: 10.1080/1536710x.2016.1124251
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Help Without Pity: The Effect of Changing Media Images on Perceptions of Disability

Abstract: This study investigated whether newer, more positive disability charity images can elicit helping behavior without producing pity. One hundred sixty-one university undergraduate students were presented with 35 older (1960-1990) and newer (1991-2010) disability charity images and completed a questionnaire about each image. Results indicate that overall, identification with depicted individuals was low; positive attitudes and perceptions of capabilities were moderate to high. Newer images led to more positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…Although such help is of great importance, the possible negative implications of pity toward individuals with disabilities should be taken into account. Pity has been found to cause “benevolence stigma,” when people are kind to others mainly because they consider them to be unfortunate and to have lower abilities then themselves (Corrigan, Edwards, Green, Ddiwan, & Penn, ; Fominaya, Corrigan, & Rüsch, ; Kamenetsky, Dimakos, Aslemand, Saleh, & Ali‐Mohammed, ). Pity may stem from paternalism and may have a negative effect on individuals with disabilities, including lower empowerment and self‐esteem (Fominaya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although such help is of great importance, the possible negative implications of pity toward individuals with disabilities should be taken into account. Pity has been found to cause “benevolence stigma,” when people are kind to others mainly because they consider them to be unfortunate and to have lower abilities then themselves (Corrigan, Edwards, Green, Ddiwan, & Penn, ; Fominaya, Corrigan, & Rüsch, ; Kamenetsky, Dimakos, Aslemand, Saleh, & Ali‐Mohammed, ). Pity may stem from paternalism and may have a negative effect on individuals with disabilities, including lower empowerment and self‐esteem (Fominaya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that helping behaviour is not necessarily contingent to stereotypical depictions that elicit pity (Kamenetsky et al 2016). Social inclusion can be achieved by communicating images of individuals with TS that are more congruent with typically developing peers’ self-image.…”
Section: Discussionmentioning
confidence: 99%
“…However, since men are expected to be strong and self-sufficient, if they are not seen as able to fulfil masculine sex-roles prevalent in most cultures, it is possible that they may be subject to more negative evaluations than women. Indeed, Kamenetsky et al (2016) found that images (without text captions) of men with disabilities elicited greater sadness, anger, disgust, guilt and lower perceptions of capabilities and rights but also, and perhaps consequently, a greater willingness to help.…”
Section: Gender and Language Typementioning
confidence: 99%
“…Broadly speaking, these may include identification with individuals depicted, emotional reactions to the images, willingness to help and include such individuals, perceptions of their capabilities, as well as whether they are entitled to the same rights accorded to the rest of society. The literature on these constructs has recently been reviewed by Kamenetsky et al (2016). The following section presents a brief summary.…”
Section: Measuring Perceptions Of Persons With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation